THE EFFECT OF DIFFERENTIATION STRATEGY, PRODUCT QUALITY, COMPETITIVENESS, AND SOCIAL CAPITAL ON BUSINESS SUSTAINABILITY OF ONLINE BASED SMES - Islam, Azmi Muhammad; Ningsih, Nikem Kurnia; Reza, Fahry; Zahran, Rifda Muthy; Yulistyono, Agus (Indo-Fintech Intellectuals: Journal of Economics and Business, 2025)
This study aims to examine the effects of differentiation strategy, product quality, competitiveness, and social capital on the business sustainability of online-based Small and Medium Enterprises (SMEs). Using a quantitative approach and Structural Equation Modeling (SEM) with SmartPLS, data were collected from owners and managers of online-based SMEs in Indonesia. The results show that all four variables—differentiation strategy, product quality, competitiveness, and social capital—have a significant and positive impact on business sustainability. These findings suggest that an integrated strategic, quality, and relational approach is essential for SMEs to thrive in competitive digital environments. The study contributes to the growing literature on digital entrepreneurship and provides practical insights for SME development and policymaking.